ALUMINIUM INDUCED OXIDATIVE STRESS AND ANTIOXIDANTS SYSTEM IN TWO BARLEY VARIETIES AND ITS ALLEVIATION THROUGH ASCORBIC ACID AND SALICYLIC ACID SEED PRIMING APPROACH: Life Science - Biotechnology - SHAHNAWAZ, MD; SANADHYA, DHEERA (International Journal of Life Science and Pharma Research, 2017)
The phytotoxic effect of various concentrations (2mM-6mM) of Al at acidic pH was investigated in terms of oxidative damage (ROS), molecules of lipid peroxidation (MDA, H2O2), non-enzymatic antioxidants (glutathione, flavonoids) and antioxidant enzyme activities (SOD, POD, Catalase) in two Barley varieties RD25522 (Al tolerant) and RD2052 (Al sensitive) and its alleviation was studied using seed priming approach with two PGR’s Ascorbic acid (AA) and Salicylic acid (SA). Both AA and SA regulate the plant growth and protect the plant against biotic and abiotic stress due to their antioxidant activity. The experiment was carried out under in vitro conditions for six days. ROS content increased significantly with increased concentration of Aluminum. Biophysical parameters like Electrolyte leakage (EL) increased while Relative Leaf Water Content (RLWC) decreased due to increased ROS and also induced lipid peroxidation which was correlated with an increased membrane injury. The antioxidant enzymes like superoxide dismutase (SOD), ascorbate peroxidase (APX), catalase (CAT), and glutathion reductase (GR) showed increased activity while pyrogallol peroxidase (POD) and nonenzymatic antioxidant glutathione, flavonoids showed declined content with increased Al concentration. These result showed increased oxidative stress under induced Al phytotoxicity and barley variety RD2552 showed tolerant nature than RD2052 against Al stress. Abbreviation- AA-Ascorbic Acid, SA-Salicylic Acid, SOD- Superoxide Dismutase, APX- Ascorbate Peroxidase, CAT- Catalase, GR- Glutathione Reductase, POD- Pyrogallol Peroxidase, RLWC- Relative Leaf Water Content, MDA- Malondialdehyde, H2O2-Hydrogen Peroxide, GSH- Glutathione